Component Development Using Topological Methods - Szabó, Kristóf (International Journal of Engineering and Management Sciences, 2023)
The article aims to briefly summarize the design aids which can be used nowadays, such as topology optimization and generative design, which are common in integrated CAD systems. A case study is used to present the results and comparisons provided by the previously mentioned methods.